6: Creating Tissue Engineered Nipples Using 3d-printed Poly-4-hydroxybutyrate (p4hb) Bioabsorbable Scaffolds Augmented With Autologous Processed Costal Cartilage. (July 2021) - Dong, Xue; Premaratne, Ishani; Gadjiko, Mariam; Berri, Nabih; Limem, Skander; Sariibrahimoglu, Kemal; Scott, Jeffrey; Spector, Jason
Abstract : Purpose: Nipple reconstruction is a vital part of breast reconstruction after total mastectomy. However, nearly all autologous tissue techniques utilized for reconstruction of the nipple are hindered by scar contracture and loss of projection of the neo-nipple. Unfortunately, engineered tissue substitutes, such as Cook Biodesign ® nipple reconstruction cylinders, have demonstrated suboptimal projection maintenance over time. Costal cartilage (CC) has been described in nipple reconstruction to maintain projection, yet has not been adopted due to the excessively firm nipple that results. Herein we propose using 3D-printed bioabsorbable P4HB (3D-P4HB) scaffolds loaded with processed CC in order to foster ingrowth of tissue that mimics the biomechanical properties of native nipples and to protect the regenerated tissue from contracture as it matures. Methods: 3D-P4HB scaffolds (diameter: 1.0cm, height: 1.0cm) were fabricated and sterilized. Patient-derived CC (discarded from DIEP procedures) was either minced (1mm 3 ) or zested (<0.2mm 3 ) in sterile fashion. Processed cartilage-filled 3D-P4HB scaffolds were subcutaneously implanted into nude rats using a CV flap technique. Additional groups consisted of empty 3D-P4HB scaffolds, 3D-P4HB scaffolds with an internal 3D latticework of P4HB filaments (rebar), and non-scaffolded (naked) cartilage. The constructs were explanted at 1, 3 and 6 months, and evaluated by gross, microstructural, histological, and biomechanical analysis. Results: All 3D-P4HB nipple reconstructions were well preserved in diameter and projection at 1, 3 and 6 months, primarily due to the persistence of the scaffold architecture throughout these time points. When compared to the non-scaffolded (naked) group, 3D-P4HB groups demonstrated significantly greater projection at 3 and 6 months (p<0.05). There were no significant differences observed in tissue volume retention between the two processed cartilage-filled 3D-P4HB groups at 1, 3 and 6 months. However, the non-scaffolded (naked) group lost a significant amount of volume in the first 3 months (38% in minced and 26% in zested, p <0.05), but remained unchanged between 3 and 6 months. Newly formed spongy fibrovascular cartilaginous tissue (with viable chondrocytes within the lacunae) was also noted in processed cartilage-filled 3D-P4HB groups. Interestingly, 3D-P4HB (rebar) scaffolds demonstrated the fastest material absorption overtime, as demonstrated by biomechanical testing and SEM analysis which verified widespread pitting on the material surface. Elastic modulus testing indicated minimal change in 3D-P4HB (rebar) scaffold stiffness at 1 month, yet a sharp decrease from 8MPa to 4MPa between 1 to 3 months. Both processed cartilage-filled 3D-P4HB scaffolds slightly increased in stiffness over 6 months within the range of 2 to 3MPa ( p >0.05). Conclusion: Using 3D-P4HB scaffolds filled with autologous processed CC, we have engineered nipples that maintain their projection and volume over time, while simultaneously allowing for the maturation of an internal structure of fibrovascular cartilaginous tissue that biomechanically mimics that of native nipples. As the 3D-P4HB scaffold gradually absorbs, data suggest that newly-regenerated tissue may resist scar contracture and maintain projection over time. Because P4HB devices for soft tissue reinforcement have previously been cleared by the FDA and possess a long track record of safety, we believe that this novel 3D-P4HB nipple reconstruction scaffold may be readily translatable to the clinic.